Career Development and Hermeneutical Inquiry: Part 1. The Framework of a Hermeneutical Approach - Young, Richard A.; Collin, Audrey (Canadian Journal of Counselling and Psychotherapy, 2011)
Hermeneutics, the practice of interpretation, has gained increased interest in the social sciences as an alternative form of inquiry. In this, the first of two papers, hermeneutical inquiry is proposed as suitable to the study of several aspects of career counselling, including career as a life-span project, its active and dynamic nature, its social and cultural dimension, and its intentionality and agency. Three specific steps of hermeneutical inquiry are addressed: the recognition of the researcher's initial framework, the identification of the actor's framework, and the construction of the interpretation. Finally, it is argued that the practice of counselling is particularly suited to hermeneutical inquiry.